Development of a quorum quenching-column to control biofouling in reverse osmosis water treatment processes - Lee, Seonki (2021)
Biofouling is recognized as one of the most problematic fouling types in reverse osmosis (RO) processes and lead to high energy requirements and operating costs. Over the past decade, many studies on membrane bioreactor (MBR) systems for wastewater applications demonstrated that disrupting cell-cell communications among bacteria, called quorum quenching (QQ), is a promising approach to inhibit biofouling of membranes. Here, we developed the QQ-column as a novel strategy to control biofouling in RO systems. The QQ-column was prepared by incorporating a recombinant bacterial QQ strain into hydrogel beads and embedding these beads inside a column. The QQ-column was installed upstream of the RO module to degrade N-acyl homoserine lactone, a quorum sensing (QS) signal, from the feed in a laboratory-scale RO system operating in total recycle mode. The QQ-column reduced the concentrations of signal molecules by ~29% in an RO system and mitigated biofilm formation (38.6% reduction of cell number) on the membrane, consequently reducing the transmembrane pressure by 50.1%. These results demonstrate that integrating QQ bacteria into columns is a practical method to control biofouling in RO systems.